PERANCANGAN TAMPILAN APLIKASI MOBILE BENGKEL STUDI KASUS ABIN MOTOR - Alghani, Ghiyats; Jimmie (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The rapid development of information technology has significantly influenced various aspects of life, including the automotive service sector. Currently, Abin Motor Workshop still relies on manual data recording, which is prone to errors and inefficiencies in purchasing spare parts and service transactions. This research aims to design and develop an Android-based motorcycle workshop information system to streamline service processes and improve customer experience. The research adopts the Waterfall development methodology, encompassing stages such as requirement analysis, system design, implementation, testing, and maintenance. Data collection methods include direct observation at Abin Motor Workshop and literature review. The system consists of two main user roles: customers and administrators, enabling customers to book services and purchase spare parts efficiently. The findings indicate that the developed system successfully optimizes service management by reducing manual errors, minimizing customer wait times, and enhancing operational efficiency. Customers can now access services remotely without visiting the workshop in person. This system significantly improves workflow efficiency and provides accurate transaction records, ensuring better customer satisfaction.